Evaluation of respiratory tract function in workers employed in the production of Enolophos - Konieczny, B (Pneumonologia polska, 1990)
An analysis of the respiratory function of workers of a chemical factory producing Enolophos was carried out. All workers were included in the study-41 men (age range 23-59 years, mean working duration 4.9 years). In 48.8% chronic bronchitis was diagnosed. Spirometric analysis was carried out using an electronical spirometer with a steady volume plethysmograph. The following along with other pulmonary mechanics parameters were assessed: compliance, airway resistance. An increase of the FEV1%VC index was seen in 34.2% and RV/TLC in 40%. Compliance was increased in 30%. Airway resistance was increased especially in subjects with chronic bronchitis and a decrease in FEV1, FEV1%VC, FEF50, FEF25 rates. In patients with decreased erythrocyte acetylcholinesterase activity only increased airway resistance was seen. The duration of working in this factory did not affect respiratory function. The results demonstrate a harmful effect of Enolophos to the lungs and airways.